Prostorsko planiranje na poti k sistemski ureditvi - Zavodnik Lamovšek, Alma (Urbani izziv, 2003)
The article deals with a broad palette of questions and issues emerging from day-to-day practice in physical planning, even in relations between national and local physical planning. The questions and issues apply to methodology, content and procedures and concern the entire system of physical planning in Slovenia. Emphasis is given to the role of planning on the local community level, authority concerning spatial development in its' territory and possibilities for mediation between national, above all, departmental interests. Questions concerning the new systems arrangement are also raised, stemming from the introduction of new planning acts and planning on the regional level, whereby the system and procedure haven't been satisfactorily solved in the new law on physical planning. In conclusion certain proposals for the establishment of a physical planning system are presented, a system which could be modern, harmonised, flexible, open and oriented towards modern solutions, as well as overcoming the rigidity of traditional procedures in physical planning.
Keywords: pravna ureditev; prostorski razvoj; prostorsko planiranje; prostorsko urejanje; Slovenia; Slovenija; spatial planning; strategija; urejanje prostora